User-centric based vertical handover decision algorithm for telecardiology application in heterogeneous networks - Yew, Hoe Tung (Penerbit UTM Press. All rights reserved., 2015)
He traditional telecardiology system which is integrated with a single wireless technology is unable to guarantee the patient always get connected to the telecardiology service provider. To overcome this problem, an adaptive user-centric based vertical handover algorithm is proposed to allow the telecardiology system operates in heterogeneous wireless technologies. The proposed algorithm guarantees the quality of service and maintains the user’s satisfaction at the highest level. The algorithm was compared with traditional quality of service based and cost based vertical handover algorithms. The results show that proposed algorithm is performed better than the traditional algorithms.